2019
DOI: 10.1016/j.fochx.2019.100029
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in physicochemical and functional properties of buckwheat straw insoluble dietary fiber by alkaline hydrogen peroxide treatment

Abstract: Highlights The untreated IDF tended to strong antioxidant properties in vitro . The changes of antioxidation might be related to specific substrates. AHP treatment could led to redistribution of monosaccharide in IDF. AHP treatment could improve physicochemical properties of IDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…However, peak intensities showed increasing trends which indicated that that crystallinity was increased as a result of exposure to enzymatic treatment. This might be because enzyme treatment caused breakage of the links between cellulose and hemicellulose leading to hydrolysis and solubilization of amorphous regions of these polysaccharides, and removal of adherent starch (Meng et al., 2019). This was also reported by Wen et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, peak intensities showed increasing trends which indicated that that crystallinity was increased as a result of exposure to enzymatic treatment. This might be because enzyme treatment caused breakage of the links between cellulose and hemicellulose leading to hydrolysis and solubilization of amorphous regions of these polysaccharides, and removal of adherent starch (Meng et al., 2019). This was also reported by Wen et al.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD patterns of the modified and non‐modified RIDF were presented in Figure 2. The sharp peaks with diffraction angles of 22° and the weak peaks with diffraction angles of 15° indicated the cellulose I form with the crystallization zone and non‐crystalline region (Meng et al., 2019). There was no significant difference in the peak position between the original RIDF and the modified RIDF, suggesting that the crystal structure of the fiber samples did not change after the modification.…”
Section: Resultsmentioning
confidence: 99%
“…Among the samples, the E‐RIDF (5.62 ml/g) had the highest WSC value (Figure 5B), which might be related to good hydrophilic ability (Park, Lee, & Lee, 2013). The WSC value of E‐RIDF significantly ( p < .05) increased by 37%, a value higher than the 2.00 ml/g for millet bran, 4.58 ml/g for ISF, 1.92 ml/g for ginger residue, and 5.31 ml/g for buckwheat bran IDF powder (Chen et al., 2019; Chu et al., 2019; Meng et al., 2019; Wang et al., 2020). The hydrolysis of cellulose and hemicellulose by cellulase and xylanase could break the β‐glycosidic bond connection, exposing more water‐binding sites and dipole forms, leading to higher WSC (Cheng et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a significant difference ( p < .05) in the WHC and SC between ULC‐30 and untreated sample. The cellulose with the smaller particles size, greater surface area, and more hydrogen bonds after ultrasonic treatment, as shown in the SEM and FT‐IR measurements, has a greater ability to surround water and therefore explains the increase of WHC (Meng et al, ; Zhao et al, ; Zhu et al, ). The increased SC may result from the degradation of cellulose by an ultrasonic treatment which can generate space‐enlarging effects (Meng et al, ).…”
Section: Resultsmentioning
confidence: 99%